Outcomes of truncus arteriosus repair and predictors of mortality - Hamzah, Mohammed; Othman, Hasan F.; Daphtary, Kshama; Komarlu, Rukmini; Aly, Hany (Journal of cardiac surgery, 2020)
Objective The objective of this study was to identify patient and hospitalization characteristics associated with in‐hospital mortality in infants with truncus arteriosus. Methods We conducted a retrospective analysis of a large administrative database, the National Inpatient Sample data set of the Healthcare Cost and Utilization Project for the years 2002 to 2017. We also sought to evaluate the resource utilization in the subgroup of subjects with truncus arteriosus and 22q11.2 deletion syndrome. Neonates with truncus arteriosus were identified by ICD‐9 and ICD‐10 codes. Hospital and patient factors associated with inpatient mortality were analyzed. Results Overall, 3009 neonates met inclusion criteria; a total of 326 patients died during the hospitalization (10.8%). Extracorporeal membrane oxygenation utilization was 7.1%. Univariate and multivariate logistic regression analyses were used to identify risk factors for in‐hospital mortality. Significant risk factors for mortality were prematurity (adjusted odds ratio [aOR] = 2.43; 95% confidence interval [CI]: 1.40‐4.22; P = .002), diagnosis of stroke (aOR = 26.2; 95% CI: 10.1‐68.1; P < .001), necrotizing enterocolitis (aOR = 3.10; 95% CI: 1.24‐7.74; P = .015) and presence of venous thrombosis (aOR = 13.5; 95% CI: 6.7‐27.2; P < .001). Patients who received extracorporeal membrane oxygenation support or had cardiac catheterization procedure during the hospitalization had increased odds of mortality (aOR = 82.0; 95% CI: 44.5‐151.4; P < .001, and aOR = 1.65; 95% CI: 0.98‐2.77; P = .060, respectively). Conclusion 22q11.2 deletion syndrome was associated with an inverse risk of death despite having more noncardiac comorbidities; this patient subpopulation also had a higher length of stay and increased cost of hospitalization.